Game-Based Learning: The Impact of Kahoot on a Higher Education Online Classroom - Altawalbeh, Khitam (Tauladan Fathimah Azzahra, 2023)
Digital games are an interactive tool within a multimedia education system and have the potential to make learning more effective and engaging, particularly for young students. The purpose of this investigation is to learn more about game-based learning. In this study, a game-based learning environment (Kahoot) was used to improve motivation, fun, engagement, and utility for learning. The research was carried out in a university course to test the effectiveness of the proposed approach on students’ learning. A total of 72 students were purposively selected. A descriptive approach was used, and a survey was distributed to the learner. The study tool consisted of 26 items in four domains; fun, engagement, motivation, and utility for learning. The findings of the investigation revealed that fun, engagement, motivation, and utility for learning were supported by game-based learning. However, no significant differences were found based on gender, the field of study, and the academic year. Relied on the results a set of recommendations was proposed.